Customers’ Intention to Use Digitalized Islamic Crowdfunding: The Case Of Bimb Sadaqa House - Karim, Norzitah Abdul; Aziry, Nur Adibah Ab; Ridzuan, Nurul Izzaty Mohamad; Jaafar, Mohamad Nizam; Muhamat, Amirul Afif (Advances in Social Sciences Research Journal, 2023)
This study aims to investigate the factors that influence BIMB customers’ intention to utilise Sadaqa House, a digitalized Islamic crowdfunding platform. This study utilised the Theory of Planned Behavior (TPB) as a conceptual framework with four (4) independent variables, namely attitude, subjective norms, perceived behavioural control, and religiosity, and one dependent variable, namely intention to use digitalized Islamic crowdfunding. BIMB clients in Selangor were sent an online questionnaire, Google Form, via several social media platforms. There was a total of 250 respondents collected. The findings revealed that subjective norm was the most influential factor in predicting consumer intention to use Sadaqa House BIMB. This was followed by an attitude indicating that supportive ideas from others, such as families, relatives, peers, and acquaintances, can influence the respondent’s choice to utilise Sadaqa House. However, perceived behavioural control and religiosity have little impact on the intention to use Sadaqa House BIMB. The results suggested that BIMB should permit all non-profit organizations, private and public sectors, and communities to contribute to this digitalized Islamic crowdfunding initiative organised by Sadaqa House BIMB. Additionally, the study suggests that more campaigns be conducted to create and promote awareness. With increased awareness, not only the individual but also the individual’s circle will be influenced to utilise this digitalized Islamic crowdfunding. This study differs from previous research in that it provides a new perspective by employing TPB and introducing a new variable, religiosity.